Continuity and Knowledge Transmission on the Northwest Coast: Insights from Wet Site EkTb-9, Triquet Island, N̓úláw̓itx̌v Tribal Area, British Columbia, Canada - Alisha Gauvreau (Ethnobiology Letters, 2025)
Paleoethnobotanical wet site investigations enhance our understanding of ancestral people's relationships with plants and how they have evolved and persisted into the present. Archaeological records of human-plant interactions were historically underutilized or underreported at sites along the Northwest Coast of British Columbia, Canada. Recent advances in interdisciplinary and community-based research have increased awareness of the importance of studying wet site assemblages in the region. Site EkTb-9, Triquet Island, within the N̓úláw̓itx̌v Tribal Area of Haíɫzaqv (Heiltsuk) Nation Territory, is the only mid-Holocene wet site on British Columbia’s outer central coast that has been subject to focused investigations. This case study provides a description of the wooden artifact assemblage from EkTb-9 with consideration in the context of other select wet sites in British Columbia. The enduring relationships that Indigenous Peoples of the Northwest Coast maintain with the varied plant communities represented in these regional wet site assemblages demonstrate continuity and perpetuation of ancestral plant-related knowledge, technologies and land management practices over several hundred generations. Collectively, these data enable an exploration of the interactivity of wet sites, social practice, and knowledge transmission spanning the early Holocene to the present day.